Literary communication as dialogue responsibilities and pleasures in post-postmodern times : selected papers, 2003-2020 - Sell, Roger D. (FILLM studies in languages and literatures,, 2020)
"As traced by Roger D. Sell, literary communication is a process of community-making. As long as literary authors and those responding to them respect each other's human autonomy, literature flourishes as an enjoyable, though often challenging mode of interaction that is truly dialogical in spirit. This gives rise to author-respondent communities whose members represent existential commonalities blended together with historical differences. These heterogeneous literary communities have a larger social significance, in that they have long served as counterweights to the hegemonic tendencies of modernity, and more recently to postmodernity's well-intentioned but restrictive politics of identity. In post-postmodern times, their ethos is increasingly one of pleasurable egalitarianism. The despondent anti-hedonism of the twentieth century intelligentia can now seem rather dated. Some of the papers selected for this volume develop Sell's ideas in mainly theoretical terms. But most of them offer detailed criticism of particular anglophone writers, ranging from Shakespeare, Ben Jonson and other poets and dramatists of the early modern period, through Wordsworth and Coleridge, to Dickens, Pinter, and Rushdie"--